Real-World Data of Different Immune Checkpoint Inhibitors for Non-Small Cell Lung Cancer in China - Miao, Kang; Zhang, Xiaotong; Wang, Hanping; Si, Xiaoyan; Ni, Jun; Zhong, Wei; Zhao, Jing; Xu, Yan; Chen, Minjiang; Pan, Ruili; Wang, Mengzhao; Zhang, Li (Frontiers in Oncology, 2022)
Background Patients treated with immunotherapy in the real-world may have significantly different responses to those meeting inclusion criteria for random controlled clinical studies. There is a partial overlap in approved indications for the use of the different immune checkpoint inhibitors (ICIs) currently available. A comprehensive assessment of the efficacy, safety and economic effects of various ICIs is a problem that clinicians need to address. Methods Analyzed real-world data was collected from non-small cell lung cancer (NSCLC) patients who were treated with ICIs from hospitalized patients in the Lung Cancer Center of Peking Union Medical College Hospital between 2018 and 2021. The objectives were to evaluate the efficacy and safety of different ICIs for the treatment of NSCLC in China and to investigate the factors affecting their curative effects. Results Overall, 351 patients were included in the retrospective study. The median PFS for the NSCLC patient cohort treated with medication regimens that included ICIs was 9.5 months, with an ORR of 47.3%. There were no significant discrepancies in efficacy and safety between the different ICIs administered. Factors that had the greatest impact on the efficacy of ICIs were the disease stage, ECOG-PS scores and treatment lines. Gender, age, smoking history, PD-L1 TPS expression, history of targeted therapy and irAEs all had a degree of influence on patient prognosis. Conclusions The study reports the experience of real-world usage of ICIs for the treatment of NSCLC patients in China. The results were generally consistent with those of clinical trials, while the efficacy and safety of different ICIs exhibited no statistically significant differences. Therefore, physicians can make a comprehensive choice based on the indications and cost of different ICIs and the preferences of patients.